Algorithmic Governance and Social Justice: The Syrian Case and the Risks of State Automation in Brazil (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This article analyzes the use of artificial intelligence (AI) and decision-making automation by public authorities, based on the SyRI (System Risk Indication) case, decided by the Hague Tribunal in 2020, and its potential repercussions in the Brazilian context. The research demonstrates that, although AI brings benefits to the administration and the judiciary—such as speed and efficiency—it also carries risks of opacity, algorithmic discrimination, and violations of fundamental rights. Comparing SyRI with Brazilian experiences, especially in the automated cross-referencing of social data and the management of welfare programs, highlights the tendency to create a "state of algorithmic suspicion," which threatens dignity and material equality. The paper concludes that transparency, democratic oversight, and legal regulation of the use of state AI are necessary, proposing preventive guidelines to avoid a "SyRI syndrome" in Brazil.